2011
DOI: 10.1016/j.mce.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial treatment of bone marrow stem cells and stromal cell-derived factor 1 improves glycemia and insulin production in diabetic mice

Abstract: Transdifferentiation of stem cells into insulin-producing cells for the treatment of diabetes have shown promising but inconsistent results. We examined the potential for attracting bone marrow stem cells (BMSCs) to the pancreas using a chemokine, stromal cell derived factor-1 (SDF-1). SDF-1 treatment markedly increased the number of GFP labeled BMSCs in the pancreas, but surprisingly, the majority was observed in liver. The liver cells had typical pancreatic endocrine cell gene expression including insulin I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…However, the effect of MSCs on glycemic control was shown to be transient by Azab et al (2). Although the mechanism of action of stem cell therapy remains elusive, the possible proposed mechanisms for improvement in β-cell mass/function include i) secretion of various growth factors, which may promote angiogenesis and stimulate resident stem cells in the pancreatic duct to differentiate into islets, ii) transdifferentiation into b-cells, and iii) pancreatic and duodenal homeobox 1 (PDX-1) upregulation, thereby enhancing islet differentiation (5,9,11). Recently, Si et al demonstrated that MSC infusion in the STZ-induced type 2 diabetic rat not only promoted β-cell function, but also ameliorated insulin resistance by enhancing the glucose transporter type 4 (GLUT-4) expression and increasing insulin receptor substrate-1 (IRS-1) and protein kinase B expression in insulin target tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of MSCs on glycemic control was shown to be transient by Azab et al (2). Although the mechanism of action of stem cell therapy remains elusive, the possible proposed mechanisms for improvement in β-cell mass/function include i) secretion of various growth factors, which may promote angiogenesis and stimulate resident stem cells in the pancreatic duct to differentiate into islets, ii) transdifferentiation into b-cells, and iii) pancreatic and duodenal homeobox 1 (PDX-1) upregulation, thereby enhancing islet differentiation (5,9,11). Recently, Si et al demonstrated that MSC infusion in the STZ-induced type 2 diabetic rat not only promoted β-cell function, but also ameliorated insulin resistance by enhancing the glucose transporter type 4 (GLUT-4) expression and increasing insulin receptor substrate-1 (IRS-1) and protein kinase B expression in insulin target tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although iPSCs have largely supplanted BMSC as a stem cell source, evaluating the pathway of islet cell regeneration though BMSC transplant inadvertently led to immune reset discovery. Following experimentally induced DM in streptozotocin-treated mice [ 158 , 159 ], streptozotocin-treated rats [ 160 ], E2f1/E2f2 mutant mice [ 161 ], and non-insulin-dependent KKAy mice [ 162 ], early BMSC treatment induced DM reversal. Despite insulin production and DM reversal, Hasegawa et al (2007) demonstrated that BMSC did not differentiate into islets but instead initiated islet regeneration from pre-existing pancreatic progenitor cells [ 163 ].…”
Section: The Promise and Future Challenges For Stem Cellsmentioning
confidence: 99%
“…The transplantation of pancreatic islets from two MHC-disparate donors was achieved in combination with IBM-BMT, resulting in the improvement of blood glucose levels and the amelioration of streptozotocin-induced DM in rats [25]. SDF-1 could potentially be used to improve the homing of stem cells and β -cell regeneration, and it improves glycemia and insulin production in diabetic mice [26]. The transplantation of insulin-producing cells from adult hBMSCs into nude diabetic mice resulted in the control of their diabetic status for 3 months [27].…”
Section: Bmsc Therapies For Type 1 Dmmentioning
confidence: 99%